Stiffness Determination of Bi- and Triaxial Flat Braided Carbon/Vinyl Ester Composites Using Micromechanics Method - Mehmet Karahan; Nevin Karahan (Tekstilec, 2024)
This paper is concerned with geometric modelling and elastic properties of 2D biaxial and triaxial braided composites. A representative unit cell (RUC) of braid architectures is first identified along with its constituents. Geometric parameters of braided structures are compared with each other. A method of inclusions with the Mori-Tanaka homogenisation was used in the determination of elastic properties of the unit cell with the Tex-Comp software. As a result, a higher amount of crimp occurs in triaxial braided structures compared to biaxial structures generated using the same yarn and construction. Therefore, the elastic modulus of the triaxial structure diminishes compared to that of the biaxial structure. However, the axial yarn reinforcement in triaxial structures ensures four times higher axial strength in the axial direction related to the biaxial structures that it provides. The results were experimentally verified.